Use of traditional medicine for the treatment of high blood pressure in rural communities - Calderon-Torres, Alfredo (2025)
The increase in high blood pressure in patients from communities in the northern region of Puno, has prompted interest in traditional medicine as a treatment support. This approach uses ancestral traditional practices aimed at controlling the disease through accessible, sustainable, and effective therapeutic options. The goal is to identify complementary alternatives for managing hypertension. The purpose of this study is to analyze the effectiveness of traditional medicine methods in assessing and controlling blood pressure through the use of ancestral therapies and healing practices from popular culture. A qualitative approach, ethnographic in scope, and non-experimental design were employed. In-depth interviews were used as the data collection technique. The units of analysis were interpreted using Atlas.Ti software and the narratives collected during fieldwork. The results of the study show that traditional medicine works effectively for treating high blood pressure. Several patients reported a notable decrease in their blood pressure after applying these therapies, and the majority expressed favorable opinions regarding their use. This finding demonstrates the value of traditional medicine in controlling hypertension and paves the way for future research in this field.